A Cross-Sectional study on risk factors for severe hypoglycemia among Insulin-Treated elderly type 2 diabetes Mellitus (T2DM) patients in Singapore. (March 2022) - Shi Min Ko, Michelle; Kit Lee, Wai; Chang Ang, Li; Goh, Su-Yen; Mong Bee, Yong; Ming Teh, Ming
Abstract: Objective: This study investigates the risk factors for severe hypoglycemia among Southeast Asian T2DM patients. Methods: Insulin-treated T2DM patients greater than 65 years old with HbA1c < 8% were recruited. They completed questionnaires detailing their experience of hypoglycemia and presence of impaired hypoglycemia awareness (IAH). Data on insulin treatment regimens, glycated haemoglobin (Hba1c) and comorbidities were also collected. Results: Of the 92 participants, 15.2% had at least one episode of severe hypoglycemia over the past year. Comparison between both groups showed that patients with severe hypoglycemia had lower Hba1c, higher Gold score (3.9 ± 1.9 vs. 2.5 ± 1.4; p < .05) and higher Hypoglycemia Fear Survey (HFS) worry score (39.1 ± 14.3 vs. 31.8 ± 11.8; p < .05 ). There were no significant differences in duration of diabetes and insulin treatment, treatment regimens and diabetes associated comorbidities except peripheral vascular disease. Furthermore, no significant differences were noted in HFS behavior score, hypoglycemia risk modifying behavior and social economic status. Conclusions: Patients with severe hypoglycemia had tighter glycemic control, greater IAH and higher worry scores regardless of treatment regimens. Clinicians may play a significant role in tightening glycemic control and influencing the risk of severe hypoglycemia. Standard structured diabetes education may help reduce the risk of severe hypoglycemia among this group of patients.